2017
DOI: 10.1111/pace.13030
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Node Dysfunction and Atrial Fibrillation: A Reversible Phenomenon?

Abstract: SND affects up to one in five patients with AF. The pathophysiological derangements in gene expression, ion channel metabolism, and alterations in myocardial architecture associated with AF may lead to anatomic and electrical changes in the region of the sinoatrial node. Ablation may improve symptoms associated with SND in patients with AF. Future randomized trials are needed to clarify the epidemiology and optimal management of patients with SND and AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 44 publications
(73 reference statements)
1
25
0
1
Order By: Relevance
“…23 In support to these notions, it seems that pulmonary vein isolation, apart from reducing AF burden and tachy-brady episodes, ameliorates sinus pauses and related symptoms as well. 23 In the present study, which included a greater number of patients than our previous pilot investigation, 15 we showed an independent association of RDW with AF in patients with SND. In addition, we demonstrated, for the first time, a significant association between γGT and AF in these patients, independently from RDW.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 In support to these notions, it seems that pulmonary vein isolation, apart from reducing AF burden and tachy-brady episodes, ameliorates sinus pauses and related symptoms as well. 23 In the present study, which included a greater number of patients than our previous pilot investigation, 15 we showed an independent association of RDW with AF in patients with SND. In addition, we demonstrated, for the first time, a significant association between γGT and AF in these patients, independently from RDW.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, up to 70% of patients implanted a dual chamber for SND may suffer AF, while in 40%–70% of SND patients atrial arrhythmias are evident at the time of diagnosis 3,4 . On the other hand, SND affects up to one in five patients with AF and it has been suggested that the structural and electrophysiological abnormalities associated with AF may provoke or aggravate sinus node dysfunction 23 . In support to these notions, it seems that pulmonary vein isolation, apart from reducing AF burden and tachy‐brady episodes, ameliorates sinus pauses and related symptoms as well 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study does not overlap with the initial and still preliminary experiences evaluating left atrial AF ablation as a way to eliminate prolonged sinus pauses at the termination of AF episodes, with an approach that combines AF ablation and cessation of antiarrhythmic drugs 7 . Overall, the role of left atrial ablation to treat patients with sinus pauses suggestive of sinus node disease associated with AF is still not defined and in the relatively small non‐randomised studies available in literature, some patients still required permanent cardiac pacing during follow‐up 8 …”
Section: Figurementioning
confidence: 99%
“…However, it is not clear whether it is the restoration of normal sinus rhythm or the cessation of antiarrhythmic or rate-controlling drugs that provides benefit. The population that would most benefit from ablation has not yet been fully characterized [26].…”
Section: Clinical Implications and Potential Treatmentsmentioning
confidence: 99%